Embedding Evidence on Conservation Interventions Within a Context of Multilevel Governance. Issue 1 (21st January 2016) - Ekroos, Johan; Leventon, Julia; Fischer, Joern; Newig, Jens; Smith, Henrik G.
Abstract: We outline a conceptual strategy for implementing conservation interventions in a multiscale, multiactor, and multilevel governance world. Using farmland as an example, we argue that conservation interventions should be implemented within a multiscale framework of guiding ecological principles. In this context, findings from multilevel governance research can inform a nuanced understanding of the role of evidence in conservation governance and decision‐making. We propose that principles of evidence‐based conservation can be used to refine guiding ecological principles across scales, thereby creating a comprehensive evidence base that underpins decision‐making. This evolving evidence base, in turn, should be operationalized by considering the fit of ecologically relevant scales to governance levels, paying explicit attention to issues such as democratic legitimacy and interplay with existing governance structures. We outline two specific steps for meeting this challenge. Drawing on a strategic combination of conservation interventions, guiding ecological principles, and insights from multilevel governance research promises to improve both the effectiveness and legitimacy of conservation action.